EFFECTS OF ANTI-INFLAMMATORY THERAPY ON BONE MINERAL DENSITY IN PATIENTS WITH ANKYLOSING SPONDYLITIS: RESULTS OF PROSPECTIVE STUDY - Tatiana A. Raskina; Olga S. Malyshenko; Oksana A. Pirogova; Viatcheslav B. Fanaskov; Marina V. Letaeva (Фундаментальная и клиническая медицина)
Aim: To evaluate bone mineral density (BMD) in patients with ankylosing spondylitis (AS) and distinct therapeutic regimens within 3 years of follow-up. Materials and Methods: We recruited 72 male patients with AS and divided them into two groups depending on the therapeutic regimen: 29 patients received infliximab and non-steroidal anti-inflammatory drugs (NSAIDs) while 43 patients received NSAIDs only. BMD was measured annually using dual energy X-ray absorptiometry. Results: Both therapeutic regimens led to an increase in BMD at the lumbar spine (LI-LIV) compared to baseline after 3 years of follow-up; however, only the combination of infliximab with NSAIDs led to an increase in BMD at the femoral neck compared to baseline. Patients who received infliximab and NSAIDs had significantly higher BMD at the femoral neck compared to those who received only NSAIDs after 3 years of follow-up. Conclusions: In patients with AS, the combination of infliximab and NSAIDs has a therapeutic advantage over NSAIDs only.